2015
DOI: 10.1111/ejn.12977
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal motor cortex excitability during linguistic tasks in adductor‐type spasmodic dysphonia

Abstract: In healthy subjects (HS), transcranial magnetic stimulation (TMS) applied during 'linguistic' tasks discloses excitability changes in the dominant hemisphere primary motor cortex (M1). We investigated 'linguistic' task-related cortical excitability modulation in patients with adductor-type spasmodic dysphonia (ASD), a speech-related focal dystonia. We studied 10 ASD patients and 10 HS. Speech examination included voice cepstral analysis. We investigated the dominant/non-dominant M1 excitability at baseline, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Future cohort studies comparing voice recordings in a larger number of samples of different ages (e.g., large samples of subjects in early, middle and late adulthood) will better examine whether age-related changes in voice can be considered biomarkers of human ageing. Furthermore, we believe that our study would provide new helpful information to clinicians to better distinguish physiologic ageing from pathological changes of the human voice in subjects affected by various speech disorders [ 77 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future cohort studies comparing voice recordings in a larger number of samples of different ages (e.g., large samples of subjects in early, middle and late adulthood) will better examine whether age-related changes in voice can be considered biomarkers of human ageing. Furthermore, we believe that our study would provide new helpful information to clinicians to better distinguish physiologic ageing from pathological changes of the human voice in subjects affected by various speech disorders [ 77 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Moreover, a recent transcranial magnetic stimulation study found abnormal left motor cortex excitability during a "readingaloud" task in adductor SD patients compared with healthy controls; no significant changes in excitability were found in the right motor cortex. 45 A recent resting-state fMRI study found significant abnormal connectivity in the left inferior parietal cortex (together with the left sensorimotor cortex) in SD compared with healthy controls. 2 This likely contributes to abnormal sensorimotor integration, loss of proprioceptive and tactile feedback, and inappropriate modulation of learned speech production present in SD.…”
Section: Unilateral Dbs For Spasmodic Dysphonia: Sufficient or Insuffmentioning
confidence: 98%
“…48,49 A significant portion of the pallidal outflow is directed to the Voa thalamic nucleus. 30 Some focal dystonias have been treated with thalamic lesions 45 and neuromodulation of that portion of the motor thalamus. 11 Since SD (also known as laryngeal dystonia) is a focal dystonia, we were surprised that Voa (pallidal outflow) thalamic stimulation produced no benefit in vocal dysfunction.…”
Section: Treating Cerebellar Dysfunction May Mediate Improvement In Sdmentioning
confidence: 99%
“…Based on previous studies in SD [3][4][5][6][7][8][9][10], we hypothesized that SD as a disorder can be distinguished from a normal state based on significant alterations within the sensorimotor network (SMN), whereas different SD forms can be categorized based on additional and combined abnormalities within the SMN and frontoparietal network (FPN). As SD is a task-specific disorder impairing a highly learned behavior, i.e.…”
Section: Introductionmentioning
confidence: 99%